WHY REGIONAL LEADERS UNDER-TRADE: KENYA-INDONESIA TIES IN A SOUTH-SOUTH CONTEXT - Kelvin Mwangi Maina; Yanyan Mochamad Yani; Anggia Utami Dewi (Intermestic: Journal of International Studies, 2026)
This article examines why Kenya and Indonesia continue to under-trade despite renewed diplomatic engagement that was marked by the opening of a Kenyan embassy in Jakarta in 2022. As regional economic actors that share South-South cooperation narratives, the two countries experience limited bilateral trade that stood at approximately $295 million in 2024, with Kenya running a significant trade deficit of about $233 million. The study employs a qualitative case study approach that draws on trade data, policy documents, secondary literature, and semi-structured interviews with a former Indonesian diplomat in Nairobi as well as students of international relations from both Kenya and Indonesia. It applies neoliberal institutionalism complemented by constructivist insights to analyse the structural and ideational constraints shaping this outcome. The findings of the study pinpoint five key hindrances: asymmetric policy priorities favouring traditional markets, weak institutional frameworks, logistical and regulatory barriers, structural trade imbalances, and enduring perception gaps. These factors collectively constrain the translation of diplomatic intent into substantive economic exchange between the two countries. The article argues, while Kenya and Indonesia rhetorically align under the Bandung Spirit and South-South cooperation, this has not materialised into meaningful economic outcomes.